2020
DOI: 10.25029/od.2020.258.19
|View full text |Cite
|
Sign up to set email alerts
|

Democratizar la gobernanza digital escolar

Abstract: El presente artículo presenta los resultados de una tesis doctoral que analiza la tecnología digital escolar en clave democrática, y desarrolla una investigación-acción para promover la participación, la inclusión y reducir las desigualdades en este ámbito.  La investigación se ha centrado en pensar, diseñar y construir prácticas digitales más democráticas en una escuela catalana diversa, con la finalidad de reducir la brecha digital que existe entre los distintos miembros de la comunidad educativa y promover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…• The second challenge is related to the idea that "without schools it isn't possible, but schools alone can't". Thus, the action research has confirmed that, on the one hand, schools can be very important actors in the construction of participation and active digital citizenship, a conclusion we share with other researchers (Beneyto-Seoane & Collet-Sabé, 2020). But it has also shown that ordinary schools do not have enough resources to guarantee material, competence and digital use access to all actors of the school community (Van Dijk, 2005).…”
Section: Discussionmentioning
confidence: 69%
“…• The second challenge is related to the idea that "without schools it isn't possible, but schools alone can't". Thus, the action research has confirmed that, on the one hand, schools can be very important actors in the construction of participation and active digital citizenship, a conclusion we share with other researchers (Beneyto-Seoane & Collet-Sabé, 2020). But it has also shown that ordinary schools do not have enough resources to guarantee material, competence and digital use access to all actors of the school community (Van Dijk, 2005).…”
Section: Discussionmentioning
confidence: 69%